Growth, productivity, and harvest quality of Sorghum (Sorghum Bicolor L.) as food and bioethanol raw material with various treatments - Rusdi, Nurul; Singgih, Bambang; Ulinuhayani, M.; Nurhidayat, Setia Permana; Triono, Budi (Indonesian Journal of Multidisciplinary Science, 2025)
The purpose of this study was to investigate the different environmental factors that influence the growth, productivity, and quality results of harvest sorghum (Sorghum bicolor L.) as material food alternatives and materials raw bioethanol. The study consisted of 3 different treatments, where each treatment produced data to examine its effect on productivity, quality results. The experiment was designed using RAKF (factorial randomized block design) experimental design with one treatment factor, the usage of biofertilizer. The results show that liming at a dose of 2.5 tons/ha (Ca1) is sufficient to cultivate on acid soils with the red-yellow podzolic type and is more optimal if using a dosage of 5 tons per hectare depending on the results of soil analysis before planting. The best sugar quality is produced in the planting treatment during the dry season, with a total sugar value of about 14.5% and the highest reduction sugar of 2.4%. The addition of lime to acidic soil and the application of chemical and biofertileizers are crucial for optimal growth, enhancing both vegetative and generative development when applied in appropriate amounts. Furthermore, exploring the physiological mechanisms behind seasonal impacts on sugar content and assessing the economic viability of different planting seasons will provide valuable guidelines for farmers seeking to maximize food production and bioethanol raw materials.